Oscillation Criteria for Even Order Neutral Equations with Distributed Deviating Argument - Siyu Zhang; Fanwei Meng (International Journal of Differential Equations)
We present new oscillation criteria for the even order neutral delay differential equations with distributed deviating argument [r(t)ψ(x(t))Z(n−1)(t)]′+∫abp(t,ξ)f[x(g(t,ξ))]dσ(ξ)=0,  t≥t0, where Z(t)=x(t)+q(t)x(t−τ). Assumptions in our theorems are less restrictive, whereas the proofs are significantly simpler compared to those by Wang et al. (2005).